Study on molten salt synthesis, microstructural determination and white light emitting properties of CoNb2O6:Dy3+ phosphor - EKMEKÇİ, METE KAAN (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2017)
Undoped, 0.5, 3 and 6 mol% Dy3+ doped CoNb2O6 powders have been prepared by molten salt method using cobalt nitrate hexa hydrate, niobium oxide, dysprosium oxide and Li2SO4-Na2SO4 salt mixture as a flux at 800 degrees C for 4h. X-ray diffraction patterns of the undoped, 0.5 and 3 mol% doped CoNb2O6 samples exhibited a single orthorhombic columbite phase, while 6 mol% Dy3+ doped powder showed minor phase. SEM-EDS results coonfirmed XRD findings and revealed smaller grain size by increasing Dy3+ concentration. Structural and luminescence properties of Dy3+ doped samples in UV-vis spectral region were studied. The emissions increased with increasing doping concentration up to 3 mol%, and then decreased due to concentration quenching effect. The color chromaticity temperature (CCT) data of all samples have been estimated in white light region and color of light appear close to yellowish-green. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Cobalt niobate; XRD; SEM-EDS; Optical properties; White LEDs; COBALT NIOBATE; LUMINESCENCE; COLUMBITE; DY3+; EU3+; TEMPERATURE; RELAXORS